Relation of vitamin D and BsmI variant with temporomandibular diseases in the Turkish population. Issue 5 (June 2021) - Yildiz, S.; Tumer, M.K.; Yigit, S.; Nursal, A.F.; Rustemoglu, A.; Balel, Y.
Abstract: Vitamin D (VD) levels and several variants in the vitamin D receptor (VDR) gene are associated with the occurrence of diseases of the bones and cartilage. The aim of this research was to study and compare the association of the BsmI variant in the VDR gene as well as VD levels in disc displacement with reduction (DDR) between patients and healthy controls. This was a case-control study, in which 104 patients of DDR and 102 healthy individuals were studied. The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) was used to diagnose temporomandibular diseases. The VDR BsmI variant was investigated, after extraction of genomic DNA, by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), and the VD level in serum was measured. The serum VD level was significantly different between the patient and the control group (mean (SD) 13.20 (11.02) ng/mL versus 18.44 (10.03) ng/mL, respectively) (p=0.008). Serum VD assessment revealed that serious vitamin D deficiency was more prevalent in the patients than the controls (50.96% versus 21.56%) (p=0.00001). Logistic regression analysis revealed that the bb genotype and b allele carriers of VDR BsmI variant were significantly associated with increased risk of DDR (p=0.022 and p=0.01, respectively). VDR BsmI BB genotype was higher in the control group than the patient group (p=0.045). Genotype distributions for BsmI variant in the controls and the patients were confirmed using the Hardy-Weinberg equilibrium equation. The BsmI variant of the VDR gene and VD deficiency play role in DDR aetiopathogenesis in a Turkish population. Vitamin D level and VDR BsmI variation may be effective in a possible genetic-based DC/TMD Axis III to be created in the future.